Review—Two-Dimensional Titanium Carbide MXenes and Their Emerging Applications as Electrochemical Sensors. Issue 3 (1st January 2020) - Yu, Tian; Breslin, Carmel B.
Abstract : MXenes, new two-dimensional transition metal carbides and nitrides, are attracting considerable attention as multifunctional materials in various research fields due to their high surface area, hydrophilicity, good mechanical properties, metallic-like conduction and adsorption characteristics, combined with the ability to tailor the surface properties with functional groups. In this review, the applications of MXenes as electrochemical sensors are summarised and discussed. The review is focused on Ti3 C2 Tx as these are the only MXenes that have so far been considered as electrochemical sensors, primarily due to the fact that they have metallic-like conduction and can be easily formed as single and multi-layered flakes through chemical etching of the parent MAX phase. The fabrication of the Ti3 C2 Tx -based sensors is first described and then followed by an account of their applications as electrochemical sensors, for the detection of small molecules, environmental contaminants and biosensors for biomedical sensing applications. Finally, their overall stability when exposed to aqueous media, which will have implications in the future development of MXene-based sensors, is discussed together with their future prospects as electrochemical-based sensors.